Educational Genres in Eastern Europe: A Comparison of the Genres in the Humanities Departments of three Countries of Three Different Universities in Three Different Countries - Bekar, Mira; Doroholschi, Claudia I.; Kruse, Otto; Yakhontova, Tatyana (Journal of Academic Writing, 2015)
The intercultural study of genres provides an opportunity not only to gain an understanding of the differences in writing cultures but also to sharpen the view on what is particular for each learning context. As little previous research has undertaken systematic comparisons of genre systems at European universities, we collected data on educational genres used in writing from the Humanities departments of two universities in Eastern European countries (Romania and Ukraine) and one in a Southeastern European country (Republic of Macedonia). A questionnaire with listed genre names was distributed at the three universities to assess the importance and the perceptions of academic genres in the respective cultures. Open questions were used to validate the results and gather hypotheses on the meaning of the mentioned genres. Results show differences in the frequencies of genre use, which, however, do not allow typifying differences in the learning/writing cultures. Genres are labelled differently and emerge from different traditions but seem to resemble a similar pool of genres in each of the studied countries.